2007
DOI: 10.1002/cncr.22854
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of meloxicam, a selective cyclooxygenase‐2 inhibitor, and ciglitazone, a peroxisome proliferator‐activated receptor gamma ligand, on the growth of human ovarian cancers

Abstract: BACKGROUND.It was recently reported that high expression of peroxisome proliferator‐activated receptor γ (PPARγ) and low expression of cyclooxygenase‐2 (COX‐2) might be involved in the inhibition of ovarian tumor progression and confirmed that PPARγ activation could suppress COX‐2 expression via the nuclear factor‐κB pathway in ovarian cancer cells.METHODS.The current study investigated whether meloxicam, a selective COX‐2 inhibitor, and ciglitazone, a ligand for PPARγ, inhibit the growth of human ovarian canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 51 publications
5
50
1
1
Order By: Relevance
“…(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) The present study has shown that meloxicam inhibited cell proliferation in situ, supported by our previous report where meloxicam inhibited proliferation of HepG2 cells in vitro. (31) Both studies have shown expression of PCNA, a key cell proliferation marker, was reduced by meloxicam.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) The present study has shown that meloxicam inhibited cell proliferation in situ, supported by our previous report where meloxicam inhibited proliferation of HepG2 cells in vitro. (31) Both studies have shown expression of PCNA, a key cell proliferation marker, was reduced by meloxicam.…”
Section: Discussionsupporting
confidence: 89%
“…(12,13) Selective COX-2 inhibitors have been regarded as a new group of anticancer drugs based on the observation that expression of COX-2 is elevated in a variety of human cancers (14)(15)(16)(17)(18) including HCC, (19,20) and COX-2 has been shown to promote growth and inhibit apoptosis of cancer cells. (21) A number of studies have investigated the use of meloxicam, a selective COX-2 inhibitor, in inhibiting growth of cancers of ovarian, (22) bladder, (23) biliary duct, (24) breast, (25) lung, (26) and colon. (27) Meloxicam has also shown anticancer activity to treat HCC in vitro and in vivo.…”
mentioning
confidence: 99%
“…The in vivo effects of meloxicam have also been reported, though not in detail (15)(16)(17). Since meloxicam has been widely used as an NSAID, its toxicity in humans as well as in animals is well known.…”
Section: Introductionmentioning
confidence: 99%
“…We also examined whether the addition of an NSAID to that regimen would further reduce osteophytic OA joint adaptations. The NSAID meloxicam is a selective cyclooxygenase 2 (COX-2) inhibitor (10), with known antiinflammatory and antiangiogenic effects (11)(12)(13). NSAIDs are prescribed primarily for the management of OA pain (14,15); however, they have also been found to have positive effects on cartilage health in OA by increasing proteoglycan and hyaluronan synthesis (16).…”
mentioning
confidence: 99%